Implications dans la collaboration, quelles dynamiques ? - Paste, Caroline; Promonet, Aurore (Revue internationale de communication et socialisation, 2025)
The work we present is a collaborative work carried out in a non-hierarchical inter-category collective bringing together professionals from the fields of education, training, and research. This collective is institutionally framed within the network of Lieux d’Éducation Associés within the Ecole Normale Superieure de Lyon (France). After introducing the subject of our research, which brings together teachers and researcher to jointly discuss their respective professional challenges, we will show how this subject and its treatment, over the course of this collaboration, produce shifts or even transformations, particularly structural ones, within the collective. What we say is based on the written record of the collaboration, which we analyse by using tools such as a positioning grid of collectives (Ria and Jacq, 2018).